2021
DOI: 10.3390/jcm10194412
|View full text |Cite
|
Sign up to set email alerts
|

Delirium in Critically Ill Patients with and without COVID-19—A Retrospective Analysis

Abstract: Background: Delirium complicating the course of Intensive care unit (ICU) therapy is a known driver of morbidity and mortality. It has been speculated that infection with the neurotrophic SARS-CoV-2 might promote delirium. Methods: Retrospective registry analysis including all patients treated at least 48 h on a medical intensive care unit. The primary endpoint was development of delirium as diagnosed by Nursing Delirium screening scale ≥2. Results were confirmed by propensity score matching. Results: 542 pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 33 publications
2
2
0
Order By: Relevance
“…We observed delirium in 22.8% across all hospitalized COVID-19 patients, and in 57.0% of the ICU-treated COVID-19 patients. Our study thus corroborates the results of previous studies that reported an overall incidence of delirium in 11%-33% of COVID-19 patients [ 9 , 11 ] and shows a higher incidence of delirium (more than 50%) for the intensive care setting [ 1 , 4 , 5 , 12 , 23 ]. Nevertheless, our study might even underestimate the incidence of delirium in the ICU, if one considers that some ICU patients were already transferred back to their referral hospitals before being weaned.…”
Section: Discussionsupporting
confidence: 92%
“…We observed delirium in 22.8% across all hospitalized COVID-19 patients, and in 57.0% of the ICU-treated COVID-19 patients. Our study thus corroborates the results of previous studies that reported an overall incidence of delirium in 11%-33% of COVID-19 patients [ 9 , 11 ] and shows a higher incidence of delirium (more than 50%) for the intensive care setting [ 1 , 4 , 5 , 12 , 23 ]. Nevertheless, our study might even underestimate the incidence of delirium in the ICU, if one considers that some ICU patients were already transferred back to their referral hospitals before being weaned.…”
Section: Discussionsupporting
confidence: 92%
“…The increase in agitation or delirium in an imminently dying state during the pandemic in our study, which may indicate terminal delirium, is in line with results from a few studies of patients with COVID-19 or critically ill patients [ 16 - 18 ]. The ability of the virus to penetrate the central nervous system and influence neurons may make patients with COVID-19 susceptible to delirium [ 16 ].…”
Section: Discussionsupporting
confidence: 91%
“…Prolonged delirium can be interpreted as either a marker of a favorable evolution, or as the positive effect of strategies that minimize prolonged sedation on patient outcomes, such as daily sedation interruptions [31]. The incidence of delirium in this population was 25%, which is lower than what is reported in other COVID-19 studies [32]. While we did not record these data, we are aware of the many difficulties in adhering to delirium prevention strategies during the peaks of ICU admissions, such as daily sedation holds and reorientation through interactions with family members [31,33].…”
Section: Patients Intubated At Admission (N = 2325)mentioning
confidence: 60%
“…31 Neurosciences and Trauma Critical Care Unit (NCCU), Anaesthesia Medical Examiner and Clinical Lead Organ Donation-Cambridge University Hospitals NHS Foundation Trust, Cambridge, UK. 32 Intensive Care Unit, Hospital Universitario de Torrejón, Madrid, Spain. 33 Universidad Francisco de Vitoria, Madrid, Spain.…”
Section: Acknowledgementsmentioning
confidence: 99%